The Influence of Using Android-Based Educational Game Software on Software Modeling Learning for Grade VIII Students at SMPN 1 BPR Ranau Tengah - Richa Meyyolis; Achmad Buchori; Ade Ricky Rozzaky; Wijayanto Wijayanto (Edumaspul: Jurnal Pendidikan, 2025)
This study was motivated by the low interest and understanding of students toward Software Modelling lessons, particularly in Grade VIII at SMP Negeri 1 BPR Ranau Tengah. The identified issue is the lack of interactive teaching media that align with the characteristics of digital-generation students. The aim of this research is to the influence of using educational game-based learning media on Android (Kahoot) to enchance student engagement and comprehension of software modeling material. The study employs a descriptive qualitative approach with observation and interviews as data collection instruments. It was conducted at SMP Negeri 1 BPR Ranau Tengah during the even semester of the 2024/2025 academic year. The findings indicate that using Kahoot as a learning media significantly increases students enthusiasm and participation. Students become more active and competitive in understanding the material, and teachers find it easier to manage the classroom dynamically. It is recommended that teachers continue developing digital learning media relevant to technological advances and student’s characteristics.